Penyuluhan Pembuatan Makanan Bergizi Nugget Daging Ayam dengan Penambahan Wortel, Jamur Tiram, dan Susu untuk Mencegah Stunting Anak Usia Dini di Desa Balukon, Kecamatan Kahayan Tengah, Kabupaten Pulang Pisau: Counseling on Making Nutritious Chicken Nugget Food with the Addition of Carrots, Oyster Mushrooms and Milk to Prevent Stunting in Early Childhood in Balukon Village, Kahayan Tengah District, Pulang Pisau Regency - Suriani, Merti; Paulini, Paulini; Mahrita, Selvie (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Counseling on making nutritious chicken nugget food with the addition of carrots, oyster mushrooms, and milk to prevent stunting in early childhood in Balukon Village, Kahanyan Tengah District, Pulang Pisau Regency, was carried out in September 2024. The activity method was lectures and demonstrations. The benefits of the activity were that Bajewung Kindergarten students in Balukon Village received improved parenting patterns from their parents, especially the provision of nutritious food to prevent stunting for: 23 parents of Bajewung Kindergarten students, 6 Kindergarten teachers, and 13 PKK cadres could pass on skills to mothers in rural areas other than parents of Kindergarten students; There was an improvement in children's nutrition, which had a positive effect on improving children's health and intelligence, thus facilitating learning and stimulation in children. The results of the hedonic test on the level of preference for the color, aroma, and taste of the nuggets showed that 95% of panelists stated that they really liked it, 5% liked it and no panelists stated that they did not like it. The presentation of the level of preference for the nugget product showed that the counseling participants and the Bajewung Kindergarten children really liked chicken nuggets added with carrots, oyster mushrooms, eggs, and milk.